Comparison of Effectiveness Between Hydraulic Distension and Manipulation Under Anaesthesia Amongst Patients of Frozen Shoulder (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To compare the results of hydraulic distention (HD) and manipulation under anesthesia (MUA) intervention in patients with frozen shoulder (FS).Methods: The study was conducted in department of orthopedics, Shakeih Zaid bin Ayan Hospital Combined Military Hospital, Rawalakot, Azad Jammu Kashmir(AJK). The duration of study was one year extending from 1st March 2018 to 28th February 2019. The design of study was randomized. The sampling technique was non probability convenience sampling. The sample size was 158 patients with 79 patients in each group randomly allocated to group A (HD) and group B (MUA). The pre and post procedure Shoulder Pain and Disability Index( SPADI) score was used to determine the outcome in both groups.Results: A total of 158 patients participated in the study, out of which 81 (51.27%) were females and 77 (48.73%) were males. They were randomly allocated to group A (HD) and group B (MUA). The mean age of the subjects in group A was 46.6 ± 8.3 years, while 46 ± 9 in group B. In group A the mean pre management score was 82.20 ±4.7 and the mean post management score was 20.6± 3.4. Out of 79 patients in group B the mean management score was 84.2 ±6.0 before surgical intervention in patients who underwent MUA, while SPADI score improved to 30.6±2.5 after intervention. The chi square test showed the p-value of 0.39 which was not significant statistically.Conclusion: The comparison of hydraulic distention and manipulation under anaesthesia depicted that both the procedures had equal efficacy in treating frozen shoulder.